4G LTE Network Performance Analysis Provider 3 In Pamekasan Using The G-Nettrack Application - Putra, Fauzan Prasetyo Eka; Ubaidi, Ubaidi; Mahendra, Mahendra; Surur, Miftahus; Rizki, Abdulloh (Brilliance: Research of Artificial Intelligence, 2024)
This research evaluates the performance of 4G LTE Provider 3 network services in Pamekasan City using the drive test method using the G-NetTrack application. The goal is to understand network performance in providing high-quality internet access in the ever-evolving digital era. This research is important because people's needs for fast and reliable internet access are increasing, especially in cities with high population density such as Pamekasan. Field measurement results show that Provider 3's 4G LTE network has good service quality with stable download and upload speeds and adequate signal strength. Drive tests were conducted by driving along predetermined routes while recording data on signal strength, internet speed, latency, and other relevant parameters. The data collected from each location was analyzed to compare the performance of various service providers. This analysis provides a comprehensive picture of network performance and can be used to provide recommendations to both consumers and other concerned parties. The conclusion of this study includes an evaluation of the performance of each provider based on the drive test results, as well as providing recommendations for future service improvements. The results of this study provide useful insights to understand and improve user experience in telecommunication connectivity in Pamekasan City, and can be used to improve user experience.